Familial Influences on Treatment and Substance Use Among Mothers Engaged in Prostitution. Issue 4 (27th August 2020) - Murnan, Aaron; Ferber, Megan Ferriby
Abstract : Objectives: This study explores how the family system, which includes family members, romantic partners, and children, influences substance use treatment decisions and behaviors among women engaged in street‐level prostitution. Background: Women engaged in street‐level prostitution can be involved in and benefit from substance use treatment; however, these women report worse treatment outcomes compared with other treatment‐seeking women. Little is known about systemic influences on women's substance use treatment, which may contribute to poor treatment outcomes. Methods: Women ( n  = 15) between the ages of 20 and 53 years participated in qualitative interviews exploring their perceptions of how their family system influenced substance use treatment decisions and behaviors. Inductive content analysis was used to analyze data and identify themes within participant responses. Results: Women reported on multiple shared experiences of how family members, romantic partners, and children directly and indirectly influenced their substance use treatment decisions and behaviors. Conclusions: Intervention efforts that engage supportive family members and children in women's treatment or support women's positive interactions with family are likely to provide unique advantages compared with individual treatment. Implications: Providers serving these uniquely vulnerable women should consider their family systems' influence when conceptualizing and intervening, in an effort to promote better long‐term treatment outcomes.